Risk Mitigation Effectiveness in Takaful and Conventional Insurance: : A Claims Ratio Comparison in Indonesia - Haya Nabila; Amin Wahyudi; Syahruddin (El-Barka Journal of Islamic Economics and Business, 2026)
This study analyzes the effectiveness of risk mitigation in Takaful (Islamic insurance) and conventional insurance in Indonesia during the 2020–2024 period, employing a comparative quantitative approach grounded in risk management theory and insurance effectiveness indicators, as measured by the claims ratio. Secondary data were obtained from the Financial Services Authority (Otoritas Jasa Keuangan/OJK), the Indonesian Sharia Insurance Association (Asosiasi Asuransi Syariah Indonesia/AASI), and the Indonesian Life Insurance Association (Asosiasi Asuransi Jiwa Indonesia/AAJI). The data were analyzed using a quantitative descriptive method and comparative ratio analysis, comparing claims ratios between Takaful and conventional insurance to examine the effect of premium growth and claims ratios on risk-mitigation effectiveness. The findings indicate that conventional insurance demonstrates greater premium stability and more effective claims management than Takaful. Meanwhile, Takaful exhibits considerable growth potential but continues to face challenges, including low market penetration, fluctuating claims ratios, and suboptimal efficiency in risk management. These findings suggest that strengthening Islamic financial literacy, enhancing product innovation, improving industry governance, and reinforcing regulatory frameworks are critical factors in improving the effectiveness of risk mitigation and the competitiveness of Indonesia's Takaful industry. Theoretically, this study contributes to the literature on risk management and financial intermediation theory by establishing the claims ratio as an empirical indicator of risk-mitigation effectiveness; practically, it offers an evidence-based reference for regulators, industry associations, and Takaful operators in formulating policies to strengthen the stability and competitiveness of Indonesia's Sharia insurance industry.